Uji Antidiabetik Daun Binahong (Anredera cordifolia (Ten.) Steenis) Pada Tikus Putih Jantan Galur Wistar (Rattus norvegicus) Yang Diinduksi Aloksan - Nurtika, Nurtika; , Riandini Aisyah, S.Si, M.Sc (2017)
Background : Binahong leaves (Anredera cordifolia (Ten.) Steenis) contain alkaloids, flavonoids, saponins and terpenoids. Main compound of Binahong leaves is flavonoids. Objective : This study aimed to know the antidiabetic effects of 70% ethanol extract of Binahong leaves (Anredera cordifolia (Ten.) Steenis) in male Wistar rats (Rattus norvegicus) induced by alloxan. Methods : This study was experimental laboratory using pre and posttest with controlled group design. Animal tests used as many as 25 male rats Wistar were divided into 5 groups. Group 1 = distilled water as a negative control, group 2 = glibenclamide 0.126 / 200 gr / BB, Group 3 = extract of 25 mg / kg, group 4 = extract of 50 mg / kg, and group 5 = extract 100 mg / kg. Initial blood glucose measurements on day 0. Result : The results of the Kruskal-Wallis test p value = 0.000 (p <0.05), means that there were differences between groups. Analysis of Post-Hoc Mann-Whitney test between groups posttest K (-) with K (+) value was p = 0.009, K (-) at a dose was 1 p = 0.009, K (-) at a dose was 2 p = 0.009, K (-) with 3 doses of the value was p = 0.674. Mann-Whitney test results showed that all doses had a significant difference compared to the negative control with p <0.05 except for the negative control group with groups dose 3 was not significant value. Conclusion : The 70% ethanolic extract of Binahong leaves at dose of 25 mg / kg, 50 mg / kg, and 100 mg / kg had the effect as antidiabetic on Wistar rats induced by alloxan. Keywords : The 70% Ethanolic extract binahong leaves (Anredera cordifolia (Ten.) Steenis), blood glucose level.